2018
DOI: 10.3390/pharmaceutics10040199
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Stabilized RIPL Peptide-Conjugated Nanostructured Lipid Carriers: Characterization, Cellular Uptake, Cytotoxicity, and Biodistribution

Abstract: As a platform for hepsin-specific drug delivery, we previously prepared IPLVVPLRRRRRRRRC peptide (RIPL)-conjugated nanostructured lipid carriers (RIPL-NLCs) composed of Labrafil® M 1944 CS (liquid oil) and Precirol® ATO 5 (solid lipid). In this study, to prevent the recognition by the mononuclear phagocyte system, polyethylene glycol (PEG)-modified RIPL-NLCs (PEG-RIPL-NLCs) were prepared using PEG3000 at different grafting ratios (1, 5, and 10 mole %). All prepared NLCs showed a homogeneous dispersion (130–280… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…It clearly indicated that the protein adsorptions of BPNLC and PNLC are significantly lower than that of BNLC and TNLC, which may be due to its improved surface hydrophilicity. It was in accordance with the previous result [57,58]. Besides, the brush configuration of PEG chains in PNLC might effectively block the movement of protein to the vicinity of the NPs, which was mainly controlled by random Brownian motion, leading to the reduced BSA adsorption [59].…”
Section: Protein Adsorptionsupporting
confidence: 91%
See 1 more Smart Citation
“…It clearly indicated that the protein adsorptions of BPNLC and PNLC are significantly lower than that of BNLC and TNLC, which may be due to its improved surface hydrophilicity. It was in accordance with the previous result [57,58]. Besides, the brush configuration of PEG chains in PNLC might effectively block the movement of protein to the vicinity of the NPs, which was mainly controlled by random Brownian motion, leading to the reduced BSA adsorption [59].…”
Section: Protein Adsorptionsupporting
confidence: 91%
“…The protein adsorption of BNLCs, BPNLCs, TNLCs and PNLCs formulation was evaluated using BSA, the most abundant protein in serum, as a model plasma protein [57]. Since, protein adsorption occurred when the NPs came in contact with the plasma, which induced the recognition of macrophages and reduction of the tumour accumulation of the NPs [46].…”
Section: Resultsmentioning
confidence: 99%
“…2c), indicating that the presence of LNCs in the filtrate would significantly interfere with the quantification of free peptide or protein using this quantification method (p = 0.005). The presence of LNCs in the filtrate has never been reported in previous publications (12,13,20,(23)(24)(25)(26)(27)(28).…”
Section: The Limitations Of Centrifugal-filtration Devicesmentioning
confidence: 64%
“…to quantify their adsorption or encapsulation rates. This is particularly true for LNCs (12,(23)(24)(25)(26)(27)(28), and the studies of LNC/NFL peptide association (13,20,24). Generally, after separation using the devices, the BCA assay or liquid chromatography is used to quantify the proportion of free NFL peptide in the filtrate and the proportion of adsorbed NFL peptide at the LNC surface is then evaluated.…”
Section: Results and Discussion A Size-exclusion Chromatography Systementioning
confidence: 99%
“…53 When it enters the cytoplasm, it will be hydrolyzed into Calcein by esterase and remain in the cell, emitting strong green fluorescence. 54 Calcein-AM is the most suitable fluorescent probe to stain living cells because of its low cytotoxicity. The excitation and emission wavelengths of Calcein are 490 nm and 515 nm, respectively.…”
Section: Live/dead Double Staining Methodsmentioning
confidence: 99%